Friday

January 30, 2015

January 30, 2015

Posted by **arun** on Saturday, March 2, 2013 at 3:58am.

Note: f∘g denotes the composition of the 2 functions.

- maths -
**Reiny**, Saturday, March 2, 2013 at 8:13amf∘g(x) = f( (g(x) )

I will assume you meant:

g(x) = 4x/(3x-2) and f(x) = (5x+6)/(2x-2)

those brackets are essential

g(4) = 16/10 = 1.6

f( g(4))

= f(1.6)

= 14/1.2 = 140/12= 35/3

**Answer this Question**

**Related Questions**

Chemistry - The rate constants for a first order decay reaction are found to be...

chemistry - The rate constants for a first order decay reaction are found to be...

Math (Trigonometry [Polar Form]) - Let z be a complex number such that z = 2(cos...

Math - Finding the Equation - If.... f(x) = x + 2 and g(x) = −x^2 + 2x &#...

Math - Int Trig - Given the functions: f(x)=2x+2 g(x)=3/x^2+2 h(x)=sqrt(x-2) ...

Chemistry - Given the following half-reactions and associated standard reduction...

Math - Algebra2 - Given the functions: f(x)=3x+2 g(x)=3/x^2+2 h(x)=sqrt(x-2) ...

Trignometry - Let θ be the angle between the x-axis and the line connecting...

Chemistry - Free-energy change, ΔG∘, is related to cell potential, E...

Chem - Calculate the standard cell potential given the following standard ...